EFEKTIFITAS PENYULUHUAN TERHADAP SANITASI WARUNG MAKAN DI SEKITAR UNIVERSITAS DIAN NUSWANTORO SEMARANG - Eni Mahawati (Dian Nuswantoro Semarang, 2012)
Background: The rise of food stalls on campus culminated in the emergence of a variety of issues, among other health problems. In Central Java has started 21 events poisoning (2006), with the number of 1269 people, and 3 patients died. Based on data from DKK Semarang mentioned that the number of patients because of food poisoning in the city of Semarang in2006 reached an average of 21.95%. The results of the initial survey of 14 food vendors on campus UDINUS in the last 3 years (2008, 2009, 2010) showed about 45% have the knowledge, practices and the availability of sanitary hygiene compliance has not been good.Method: This is a â€œquasi experimental researchâ€ with â€œone group pre-post test designâ€. Using the observation method of data collection / survey with questionnaires. Purposive sample isdetermined, as many as 25 food stalls crowded. Processing and data analysis performed with SPSS for windows. Data were analized with â€œ Wilcoxon test â€œ to know about counseling effectiveness of food stall sanitation.Result: Based on the result of this research was known that there has been improvement of motivation, knowledge, awareness of hygiene and sanitation practices of food stalls target. Based on the results of data processing and analysis can be seen that the general sanitary conditions of hygiene that still needs to be fixed to respondents to the ideal standard sanitaryaspects of the washing, sanitizing processing and sanitary serving / food packaging.Conclusion: To optimize achieving certification stalls it is advisable need assessment for immediate assistance and facilitation to improved hygiene practices and improved sanitation facilities as a series of subsequent certification process that is well worthy of certification for food service businesses. In addition to do research on the number of germs as outcome of food hygiene and sanitation.Keyword : Food hygiene,Food sanitation,Food stalls, Counseling Effectiveness